2004
DOI: 10.1074/jbc.m403526200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repressor DREAM Interacts with Thyroid Transcription Factor-1 and Regulates Thyroglobulin Gene Expression

Abstract: Tissue-specific gene expression depends on the interaction between tissue-specific and general transcription factors. DREAM is a Ca 2؉ -dependent transcriptional repressor widely expressed in the brain where it participates in nociception through its control of prodynorphin gene expression. In the periphery, DREAM is highly expressed in the thyroid gland, the immune system, and the reproductive organs. Here, we show that DREAM interacts with thyroid-specific transcription factor TTF-1 and regulates the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 49 publications
6
76
0
1
Order By: Relevance
“…Dyrk1a is a multifaceted kinase involved in growth control (FernandezMartinez et al, 2015) and is a central player in the Hippo pathway regulating organ size (Dick and Mymryk, 2011). In this process, Dyrk1a interacts with Dream (Kcnip3), a transcriptional repressor that is also known to suppress thyroid function by downregulating thyroid-specific gene expression (Rivas et al, 2004;D'Andrea et al, 2005). This suggests a putative role for Dream in thyroid developmental growth and differentiation that warrants further investigation.…”
Section: The Proliferation Of Thyroid Progenitors and Follicular Precmentioning
confidence: 99%
“…Dyrk1a is a multifaceted kinase involved in growth control (FernandezMartinez et al, 2015) and is a central player in the Hippo pathway regulating organ size (Dick and Mymryk, 2011). In this process, Dyrk1a interacts with Dream (Kcnip3), a transcriptional repressor that is also known to suppress thyroid function by downregulating thyroid-specific gene expression (Rivas et al, 2004;D'Andrea et al, 2005). This suggests a putative role for Dream in thyroid developmental growth and differentiation that warrants further investigation.…”
Section: The Proliferation Of Thyroid Progenitors and Follicular Precmentioning
confidence: 99%
“…The mechanism by which DREAM transactivates the GFAP promoter in response to calcium is likely to involve changes in protein conformation (Carrió n et al, 1999;Osawa et al, 2001Osawa et al, , 2005 that could be stabilized by interactions with other proteins bound in close proximity (Rivas et al, 2004;Gomez-Villafuertes et al, 2005;Scsucova et al, 2005). Of note, the transcription factor nuclear factor-I is important for GFAP expression and occupies a site in the GFAP promoter located adjacent to DRE2 (Cebolla and Vallejo, 2006).…”
Section: Dream As a Transcriptional Transactivator Of The Gfap Genementioning
confidence: 99%
“…Recent studies revealed that in addition to direct binding to DNA through downstream regulatory elements (DRE), DREAM can also interact and modulate the action of transcriptional factors through protein-protein interaction (Ledo et al, 2002;Rivas et al, 2004;Zaidi et al, 2006). In the NSE region of the GnRH promoter, there are no sequences that offer a high degree of homology to consensus DRE sequence.…”
Section: Emsa Analysis Of Dream Binding To the Oct1bs-a Sitementioning
confidence: 99%